The Influence of Brand Image and Brand Trust on Purchase Decisions of McDonald's in Surabaya - Sauqy, Muhammad Syafiqus; Ariescy, Reiga Ritomiea (Manunggal Halim Jaya, 2026)
This research examined the influence of brand image and trust on purchasing decisions at McDonald's in Surabaya. The research method used is quantitative, with data collection techniques through questionnaires from 112 respondents in East Surabaya. The sampling technique used in this research is non-probability sampling in the form of quota random sampling. Data were processed using Smart Partial Least Squares (SmartPLS) software. The test results show a significant influence of brand image on purchasing decisions, while brand trust has an insignificant effect.